Preparation of MWCNTS/Cr2O3-NiO Nanocomposite for Adsorption and Photocatalytic Removal of Bismarck Brown G Dye from Aqueous Solution - Emman Jassim Mohammad; Mohanad Mousa Kareem; Abbas Jasim Atiyah Lafta (Universitas Gadjah Mada, 2020)
This work describes the synthesis of nanocomposites of multiwall carbon nanotubes (MWCNTs) with co-oxide nanocomposite (MWCNTs)/MO. These nanocomposites were prepared using a simple evaporation and drying process. The obtained composites were characterized using X-ray diffraction (XRD), Atomic force microscopy (AFM), Fourier Transform Infrared Spectroscopy (FTIR), and scanning electron microscopy (SEM). The activity of the prepared composites was investigated by following the removal of Bismarck brown G dye (BBG) from aqueous solution via adsorption processes and photocatalytic reactions. Different reaction parameters were performed such as the effect of dosage of the used nanocomposite, pH value, and effect of temperature. In addition to that adsorption isotherms and reaction kinetics were investigated. The efficiency of photocatalytic dye removal over the prepared composites was 99.9% after one hour of reaction at the optimal conditions which were mass dosage (0.03 g), pH (5), and temperature (303 K). The adsorption isotherm data were fitted with Langmuir isotherm and the kinetic data were fitted with the pseudo-second-order kinetic model.